2019
DOI: 10.1002/anie.201900823
|View full text |Cite
|
Sign up to set email alerts
|

Direct Zinc Finger Protein Persulfidation by H2S Is Facilitated by Zn2+

Abstract: H2S is a gaseous signaling molecule that modifies cysteine residues in proteins to form persulfides (P‐SSH). One family of proteins modified by H2S are zinc finger (ZF) proteins, which contain multiple zinc‐coordinating cysteine residues. Herein, we report the reactivity of H2S with a ZF protein called tristetraprolin (TTP). Rapid persulfidation leading to complete thiol oxidation of TTP mediated by H2S was observed by low‐temperature ESI‐MS and fluorescence spectroscopy. Persulfidation of TTP required O2 , wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…[27] In contrast, we have also reportedt hat Cu I Cl disrupts the Zn II 2 -TTP-2D/RNA complex. [27] In contrast, we have also reportedt hat Cu I Cl disrupts the Zn II 2 -TTP-2D/RNA complex.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[27] In contrast, we have also reportedt hat Cu I Cl disrupts the Zn II 2 -TTP-2D/RNA complex. [27] In contrast, we have also reportedt hat Cu I Cl disrupts the Zn II 2 -TTP-2D/RNA complex.…”
Section: Resultsmentioning
confidence: 99%
“…This protective effect of RNA on the zinc sites/reactivity of Zn II 2 ‐TTP‐2D was also observed in studies performed by our laboratory that examined the reactivity of the signaling molecule H 2 S with TTP. We found that H 2 S modifies Zn II 2 ‐TTP‐2D alone, but does not react with Zn II 2 ‐TTP‐2D/RNA . In contrast, we have also reported that Cu I Cl disrupts the Zn II 2 ‐TTP‐2D/RNA complex .…”
Section: Resultsmentioning
confidence: 99%
“…Recent work reveals that this mechanism is used to reactivate enzymes requiring a catalytically active ferrous heme from the inactive ferric state, formed during turnover (121). Additionally, HS • can be formed by the reaction of H 2 S with superoxide radical anion O 2 or with cysteine-coordinated Zn(II) sites in proteins (122). Fe III -heme has also been shown to result in formation of thiosulfate and hydropolysulfide species in mammalian systems ( Fig.…”
Section: Biogenesis and Clearance Of Organic Rss In Bacteriamentioning
confidence: 99%
“…Therefore, the impact of zinc binding on thiol accessibility and reactivity needs to be evaluated on an individual basis. Indeed, there are examples of protective effects of zinc binding on cysteine modification, e.g., alkylation by iodoacetamide or oxidation 58, 65 , but also cases in which modification is promoted, e.g., persulfidation by H 2 S 65 . This interplay can be even more complex in the cellular context, where prooxidant and antioxidant actions of zinc can take place depending on the cellular context and zinc levels 44 .…”
Section: Resultsmentioning
confidence: 99%